2008
DOI: 10.1088/0022-3727/41/16/165504
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study of using external fluid loading on a vibrating tube for measuring suspended sediment concentration in water

Abstract: This paper presents an exploratory study of using external fluid loading on a vibrating tube for measuring the suspended sediment concentration (SSC) in bodies of water such as rivers and reservoirs. This new measuring concept provides an opportunity for an automated on-site monitoring of the conditions in a body of water by taking the fluid sample instantaneously in the area surrounding the vibrating tube. The physical properties of the fluid sample are those of the fluid that naturally flows around the tube,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Hsu et al [35] found that the variations in dissolved solids concentration, water temperature, water pressure, flow rate, salinity, and debris on the walls of vibrating tube affect the resonance frequencies of immersed vibrating tubes considerably.…”
Section: Vibrating Tubes-based Cmtmentioning
confidence: 99%
See 1 more Smart Citation
“…Hsu et al [35] found that the variations in dissolved solids concentration, water temperature, water pressure, flow rate, salinity, and debris on the walls of vibrating tube affect the resonance frequencies of immersed vibrating tubes considerably.…”
Section: Vibrating Tubes-based Cmtmentioning
confidence: 99%
“…Hsu et al [35] presented a detailed theoretical analyses and measurement issues for practical application of vibrating tube technique and concluded that it is effective for SSC measurement in field applications. Bishwakarma and Stole [12] applied vibrating tubes technology for sediment monitoring in hydropower plant using a tool named ''Sediment Monitoring and Operation Tool for Hydro projects" (SMOOTH); the main sensor is a Coriolis Mass Flowmeter (CMF), that measures the density of flowing fluid through vibrating tubes (Fig.…”
Section: Vibrating Tubes-based Cmtmentioning
confidence: 99%
“…Currently, several monitoring practices have been developed for evaluation of settling behaviour of different suspensions, including bottle sampling, [8] pump sampling, [9] optical based on transmission [10] or scattering [11] of light, acoustic, [12,13] laser diffraction, [14] pressure difference, [15] spectral reflectance, [16] digital image and digital holographic image, [17][18][19] electrical properties, [20,21] vibrating tubes, [22] nuclear, [23,24] micro-tomography, [25] X-ray computer tomography (CT), [26] nuclear magnetic resonance (NMR), [27,28] and magnetic resonance imaging (MRI). [29][30][31] The pros and cons of these practices are reviewed elsewhere.…”
Section: Introductionmentioning
confidence: 99%